The essence of goodwill in respect business entities - Картавцева, Юлія Валеріївна; Лучка, Ігор Юрійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
An attempt to define the essence of goodwill, as well as to explore the content of this phenomenon in relation to business entities. Violation of the rights to the business reputation is viewed from the economic and legal position – in terms of ensuring a competitive business environment. Results of the study can be used in the practice of the bodies exercising the protection of business reputation of business entities. Most authors consider reputation of civil legal positions; problems reputation entities insufficiently developed. This leads to negative consequences in economic activity, violations competitive basis, negatively affects economic development. This article attempts to define the essence of goodwill and explore the content of this phenomenon in relation to business entities. Proposals for attributing reputation to the objects of IPR legislation attempts to define the essence of goodwill in respect of undertakings that will enable its measurement. Proved that determine the nature and creating opportunities DR measurement should be undertaken on the basis of the Commercial Code, the Law of Ukraine of 28.12.2004 "On Profit Tax" in the definition of goodwill and others. Based on analysis of these regulations should be amended to ch. 1 of Article 1116 Civil Code of Ukraine "subject of a commercial concession," noting that the subject of a commercial concession is the right to use intellectual property rights, trademarks, industrial designs, inventions and works, trade secrets and business reputation. It should provide a definition of DR, indicating that its contents are marking, promotional materials, packaging, product appearance, product name, commercial (brand) names, trademarks (for goods and services) of packaging products and periodicals others refer to an entity that already started using them, which led or may lead to confusion with the activities of the entity; appearance of the product, as well as better management quality, new technologies. This definition is appropriate to include in the Commercial Code as an independent legal institution. Definition reputation in the legal sense will completely recreate the essence of its purpose. It is alleged that by creating an appropriate legal institution under commercial law will be able to consolidate the economic entities the power to require integrity reputation, which is to prohibit any action that may be affected by this non-proprietary benefit. Definition reputation in the legal sense and the possibility of measuring both the intangible benefits will extend to DR property rights provided for intellectual property rights: the right to use intellectual property rights; the author's exclusive right to authorize the object IPR and author the exclusive right to prevent unauthorized use of intellectual property rights, including prohibit such use; IPR other property rights established by law. However, under use of intellectual property refers to any form of putting it into economic circulation.